2017
DOI: 10.1111/apt.14204
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of 8‐ or 12‐weeks of ledipasvir and sofosbuvir in real‐world treatment‐naïve, genotype 1 hepatitis C infected patients

Abstract: In treatment-naïve HCV genotype 1 patients, SVR was 95% in those treated for either 8 weeks or 12 weeks with ledipasvir and sofosbuvir. 8 week ledipasvir and sofosbuvir can reduce costs without compromising outcomes for those patients who qualify for such regimen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
1
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 31 publications
1
24
1
4
Order By: Relevance
“…Current Australian guidelines are similar to internationally accepted indications for an 8‐week course of sofosbuvir/ledipasvir for genotype 1 subjects with a viral load <6 million IU/ml, at clinician discretion. Our finding of 98.3% SVR12 in this group exceeds published Phase IIb and real‐world studies of 88‐94% . The more frequent use of fibroelastography in detecting advanced fibrosis in our cohort rather than FIB‐4 definitions of cirrhosis may be one potential reason for this .…”
Section: Discussioncontrasting
confidence: 50%
“…Current Australian guidelines are similar to internationally accepted indications for an 8‐week course of sofosbuvir/ledipasvir for genotype 1 subjects with a viral load <6 million IU/ml, at clinician discretion. Our finding of 98.3% SVR12 in this group exceeds published Phase IIb and real‐world studies of 88‐94% . The more frequent use of fibroelastography in detecting advanced fibrosis in our cohort rather than FIB‐4 definitions of cirrhosis may be one potential reason for this .…”
Section: Discussioncontrasting
confidence: 50%
“…SVR12 rates were nearly identical (93.6% and 93.5%, respectively), suggesting that 8‐ and 12‐week courses of sofosbuvir/ledipasvir were equally effective, in line with EASL recommendations . Similarly, a real‐world cohort study of ledipasvir plus sofosbuvir in 826 genotype 1‐infected, treatment‐naïve patients showed no difference in SVR rates between the 2 durations (both 95%) . High SVR12 rates were also reported in the HCV‐TARGET population, supporting the 8‐week treatment regimen for eligible patients .…”
Section: Efficacy In the Real‐world Settingmentioning
confidence: 66%
“…Current EASL guidelines recommend an 8‐12 week sofosbuvir/ledipasvir regimen in treatment‐naïve patients with genotype 1 . This regimen has been evaluated in several large‐scale real‐world studies with different durations, which also demonstrate high SVR rates and show that some subgroups may achieve an SVR with an 8‐week regimen …”
Section: Efficacy In the Real‐world Settingmentioning
confidence: 99%
“…Recent real-world studies on treatment of HCV genotype 1 (HCV-1) infection demonstrated that 12 weeks of SOF/LDV, SOF + DCV or SOF/VEL is efficient for treatment of the HCV-1 infection in non-cirrhotic patients without previous history of HCV antiviral therapy (2,5,(10)(11)(12). Treatment with suboptimal regimen of SOF + Pegylated Interferon (PegIFN) + RBV with around 90% efficacy in HCV-1 is not recommended anymore (3).…”
Section: Update On Treatment Of Hcv Genotype 1 and 4 Infectionsmentioning
confidence: 99%